Glucocorticoid-induced osteoporosis management among seniors, by year, sex, and indication, 1996–2012. Issue 12 (December 2015) - Albaum, J.; Lévesque, L.; Gershon, A.; Liu, G.; Cadarette, S.
Abstract Summary We identified that glucocorticoid-induced osteoporosis management (bone mineral density testing or osteoporosis treatment) among seniors improved among men (2 to 23 %) and women (10 to 48 %) between 1996 and 2007, and then remained relatively stable through to 2012. Differences were also noted by indication (from a low of 21 % for respiratory conditions to a high of 41 % for rheumatic conditions). Purpose The aim of our study was to describe the proportion of chronic oral glucocorticoid (GC) users that receive osteoporosis management (bone mineral density test or osteoporosis treatment) by sex and over time. Methods We identified community-dwelling older adults initiating chronic oral GC therapy in Ontario using pharmacy data from 1996 to 2012. Chronic GC use was defined as greater than or equal to two oral GC prescriptions dispensed and ≥450 mg prednisone equivalent over a 6-month period. Osteoporosis management within 6 months of starting chronic GC therapy was examined by sex, year, indication for therapy, and osteoporosis management history. Results were summarized using descriptive statistics. Results We identified 72, 099 men and 95, 975 women starting chronic oral GC therapy (mean age = 74.9 years, SD = 6.5). Approximately two thirds of patients (65 %) received ≥900 mg within the 6-month chronic use window. GC-induced osteoporosis management increased from 2 to 23 % (men) and 10 to 48 % (women) between 1996 and 2007, and then remained relatively stable through to 2012. A higher proportion of patients with prior osteoporosis management were managed within 6 months (56 % men, 67 % women) of chronic GC use, compared to patients without prior management (12 % men, 23 % women). Patients with rheumatic disease were managed most commonly (41 %), and patients with respiratory conditions were managed least commonly (21 %). Conclusions GC-induced osteoporosis management improved significantly over time for both sexes yet remains low. Significant care gaps by sex and between clinical areas represent a missed opportunity for fracture prevention among patients requiring chronic GC therapy.